Typification and nomenclatural notes on Bornean Timonius (Rubiaceae: Guettardeae) - Chen, Junhao; Wong, Khoon Meng (Phytotaxa, 2020)
As part of a revision of Timonius in Borneo, the types of all relevant names were evaluated. Lectotypes are designated for 14 names in Timonius, including synonyms for accepted names. An erroneous original type citation is corrected and the nomenclatural history of a few names is clarified.